(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The major goal of this study is to look at HDFC (Housing Development Finance Corporation)bank’s corporate governance policies and determine the link between market value and operatingperformance in India. The exploratory design was employed. One bank was chosen for this study basedon its market capitalization. A five-year period (from 1 April 2021-22 to 31 March 2022-23) has been takeninto account for the purposes of data analysis. This research is based on secondary data in order toexamine the link between market value and operational performance. Secondary data was gathered frombank websites, the Securities and Exchange Board of India, and other secondary data sources such asjournals, books, newspapers, and magazines. For the purpose of analysis, the data was examined usingMean, percentage, correlation analysis, t-test, and multivariate regression. The sales and CG of HDFCbank have a substantial positive correlation at the level of significance, with R multiple correlationcoefficient of 0.664, R2 of 44.6 less than 50, indicating that the model is not valid and that the influenceof CG on HDFC bank sales is statistically significant. The HDFC bank’s PAT and sales have aconsiderable positive association. During the research period, the average CG Score was 98 percent.HDFC Bank’s CG Performance was 100 percent in all years from 2021-22 to 2022-23, with the exception of2021-22. CG has no statistically significant effect on PAT or DPR. As a result, HDFC Bank shouldincrease its sales revenue, profits after taxes, and maintain an optimal dividend policy in order tomaximize corporate excellence and, as a result, increase the CG (Corporate Governance)